Factors influencing two-way referral between hospitals and the community in China: A system dynamics simulation model. (September 2018) - Li, Meina; Zhang, Yi; Lu, Yang; Yu, Wenya; Nong, Xin; Zhang, Lulu
Background: Two-way referrals between hospitals and community healthcare systems (CHSs) are important for optimizing the distribution of medical resources and enabling resource sharing, but referrals are always from CHSs to hospitals. A referral from the hospital to the community is rare in China; this has a highly negative impact on the long-term development of the Chinese health services. The aim of this study was to address influence factors in hospital–community referrals. Methods: We constructed a system dynamics model to address the problem of the two-way referral between hospitals and CHSs and identified potential countermeasures and possible solutions. The Vensim DSS program was used to construct a system dynamics model to represent the problem through model description, causal loop diagrams, and stock and flow diagrams. Results: The model was used to perform intervention experiments, in which the influence on all the sectors of referrals could be observed by changing the system parameters. The experimental results showed a greater difference in medical costs between hospitals and CHSs, more investments to CHSs, higher levels of medical insurance of CHSs, and more referrals from hospitals to CHSs. Conclusions: The system can widen the price gap between hospitals and CHSs, increase information flow, improve medical insurance level of CHSs, and elevate the current level of CHSs through enabling two-way referral between hospitals and CHSs.